2021
DOI: 10.1186/s41016-021-00235-3
|View full text |Cite
|
Sign up to set email alerts
|

The increasing expression of GPX7 related to the malignant clinical features leading to poor prognosis of glioma patients

Abstract: Background Glioma is the most common malignant brain tumor in adults. The standard treatment scheme of glioma is surgical resection combined alternative radio- and chemotherapy. However, the outcome of glioma patients was unsatisfied. Here, we aimed to explore the molecular and biological function characteristics of GPX7 in glioma. Methods The multidimensional data of glioma samples were downloaded from Chinese Glioma Genome Atlas (CGGA). RT-qPCR m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…It has also been reported the expression levels of GPX7 in glioma tissues were higher than those in normal brain tissues. Elevated expression levels of GPX7 led to poor prognosis of glioma patients [10]. These ndings are consistent with ours.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has also been reported the expression levels of GPX7 in glioma tissues were higher than those in normal brain tissues. Elevated expression levels of GPX7 led to poor prognosis of glioma patients [10]. These ndings are consistent with ours.…”
Section: Discussionsupporting
confidence: 91%
“…Glutathione peroxidase-7 (GPX7) is important in alleviation of the damage associated with ROS to body cells and is also involved in maintaining body redox homeostasis [7]. Studies have shown that the differential expressions of GPX7 are associated with some tumors, including breast cancer [3], gastric cancer [8], esophageal cancer [9], glioma [10] and hepatocellular carcinoma [ 11] among others. Although GPX7 gene expression and its transcription characteristics have been detected in various cancers, studies on GPX7 expression in cancers are limited by small sample sizes, or are focused on a single or limited number of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have explored the relationship between GPX7 and specific tumors. 14 , 31 , 32 Our study revealed that the expression of GPX7 was elevated in multiple tumor tissues, including LGG, GBM, BRCA, ESCA, LIHC. Yao et al reported that the expression of GPX7 was higher in glioma tissue compared with normal brain tissue.…”
Section: Discussionmentioning
confidence: 69%
“…Yao et al reported that the expression of GPX7 was higher in glioma tissue compared with normal brain tissue. 32 Previous studies have shown that GPX7 has potential tumor suppressor effects in gastric cancer and esophageal adenocarcinoma. 12 , 14 , 33 Down-regulation and dysfunction of GPX7 expression in esophageal cells increase ROS level and oxidative DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…( 7 ) showed that GPX7 had an overexpression in hepatocellular carcinoma tissues. In glioma, only one bioinformatic study reported that GPX7 was a potential prognostic molecule based on Chinese Glioma Genome Atlas (CGGA) database ( 8 ). However, the mechanisms by which GPX7 might exert its actions in the development of glioma remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%